A fraseologia dos termos jurídico-financeiros no gênero contrato inglês/português - François, Michel Emmanuel Félix (2005)
The purpose of this dissertation is to identify and describe the phraseology in commercial contracts. The phraseology units represent a chain of specialized characters, formed by variable and invariable elements within a field of knowledge, according to their properties of frequency and fixation. This study is based upon the approach of Gouadec (1994), which establishes the differences between the phraseology units conditional to their inclusion in terminological matrix or not. The distribution and behavior of the phraseology units, in commercial contracts collected in Brazilian companies, are taken into account, based upon the studies of Bhatia (1993), referring to the categorization of genres in legal settings. It is observed that phraseology in contract genre constitutes a proper categorization, which varies in accordance with the structural functions of the contract. This dissertation also suggests some further research to be carried out in the field of Terminology.